Histological Changes In The Ovary Of The Bat Taphozous Kachhensis (Dobon) During Various Phases Of Reproductive Cycle (Applied Biological Research, 2011)
The histological structure of ovary of the bat Taphozous kachhensis (Dobon) was studied during different phases of reproductive cycle. The  female mature bats were collected; dissect-out and respective organ were  fixed in bouins fixative for histological observation. During quiescence  period no significant histological changes were observed in both ovaries,  but during breeding period right ovary showed the development of  Grafian follicle while in left ovary only some multilaminar follicles were  seen. The study revealed that there was dominance of right ovary over  left one; and right ovary seems functional during breeding cycle. The  persistence of functional corpus luteum in the ovary of T. kachhensis throughout gestation indicated that the ovary may be the major source of  progesterone, necessary for the maintenance of pregnancy in the species.
Keywords: Bat; corpus luteum; Grafian follicle; histology; ovary; Taphozous kachhensis